50 ways to use technology enhanced learning in the classroom practical strategies for teaching - Atherton, Pete (Learning Matters/SAGE, 2018)
This is a practical guide to the use of technology enhanced learning (TEL) in the classroom. Introducing 50 ways to use technology for learning. Areas covered include: Gamified learning; Social media; Video streaming; The flipped classroom; Instant feedback tools; And many more. Guidance on how to use these technologies for learning is complemented by an exploration of their impact on learning. For each example, the opportunities for evidencing progress are evaluated -- Provided by the publisher.